Strategies To Improve Students' Ability To Think Critically On Learning Outcomes Economic Subjectsin Class X Ma. Miftahul Hidayah - Puspitasari, Yesi; Hoirotun, Hoirotun; Permatasari, Intan; Imani, Halisatil; Hakim, Lukmanul; Fitriani, Desy; Fitriati, Desy (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Critical thinking is a skill that students must have. The purpose of this study was to describe the level of critical thinking skills of grade X students of MA Miftahul Hidayah. The method used is descriptive method with data collection techniques through distributing questionnaires in the form of questionnaires and post-test questions related to critical thinking skills. The population in this study were all grade X students while the sample size was 19 students. Based on this study, it was found that the level of critical thinking of grade X students of MA Miftahul Hidayah was in the moderate category. Thus, better guidance needs to be done in order to improve students' critical thinking skills, for example by applying the project-based learning method which is believed to be more effective in encouraging the improvement of critical thinking skills.